The Education of Ants: the far right and the social media (Simbiótica. Revista Eletrônica, 2025)
The article starts with the question: what is educational about the actions of contemporary far right groups on social media, and what are the implications for the future of democracies? To address this question, it draws on the ideas of idolatry (Souza, 2020) and the information regime (Han, 2018). It is organized into three sections. First, it seeks to understand reactionism from the perspective of the digitisation of life. Second, it analyses three cases: the Five Star Movement in Italy, the Donald Trump's 2016 campaign in the United States, and the actions of Jovem Pan in Brazil. Together, these cases demonstrate how reactionary leaders and movements have used digital environments to manipulate information and consolidate their political power. The third part proposes a reflection on the effects of these movements, questioning the impacts of political radicalisation and disinformation on the public sphere and the very idea of democracy. It concludes that contemporary far-right movements operate under the guise of freedom and spontaneity, educating individuals to accept a quantitative conception of ‘truth,’ the naturalisation of market relations, and an idea of democracy as the imposition of the will of the majority on minorities
Keywords: far right; social media; idolatry; subjectivities